Sacral neuromodulation in patients with detrusor underactivity: Is biological sex an indicator - ONUR, AHMET RAHMİ (My University, 2022)
Objectives This study aimed to report sacral neuromodulation (SNM) outcomes in detrusor underactivity (DU). Methods A multicentric, multinational, retrospective case series was conducted between March 2017 and June 2021 in three different referral centers. Initial test phase stimulation included either a percutaneous nerve evaluation (PNE) or an advanced lead evaluation test phase (ALTP) before permanent SNM implantation. The test phases were performed under local anesthesia, either in the outpatient (PNE) or operating room (ALTP), in the prone position, which was implanted in the third or fourth sacral foramina under fluoroscopic guidance. Patients with favorable response to the initial test phase during the first 2 weeks underwent the implantable pulse generator (IPG) implantation (Medtronic neurostimulation generator device InterStim (TM)). Favorable response was defined as >= 50% improvement in symptoms, frequency of clean intermittent catheterization (CIC) and/or decrease in postvoid residual (PVR), increase in voided volume, or improvement in bladder voiding efficiency (BVE) based on the bladder diary. Results Fifty-eight patients were recruited with a mean age of 39.95 +/- 15.28 years. Among the 58 cases, 36 (62.1%) patients responded to the initial stage. Of these, 12 patients (30.8%) with non-neurogenic etiology and nine patients (52.9%) with neurologic etiology did not respond to the initial test phase; thus, they did not undergo full implantation (p = 0.141). Voided volume, PVR, and the median maximum flow rate (Qmax) improved significantly (p < 0.001) in both sexes; however, there was no statistical difference between both genders. Most female cases (78.3%), and nearly half of the men (51.4%), responded to the test phase and were candidates for the IPG phase. Among the 35 cases who underwent IPG, 27 patients (72.2% of males, and 77.8% of females; p = 0.700) had a favorable response to IPG. 46.6% of patients had a successful outcome at the end of the study. Conclusion This multicentric study showed that SNM effectively and safely provided symptom improvement in refractory DU in males similar to females which is an important finding as previously it has been suggested that SNM works better in nonobstructive urinary retention in women and not in women.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Urology; detrusor underactivity; outcome; sacral neuromodulation; underactive bladder; BLADDER OUTLET OBSTRUCTION; CONTRACTILITY; etrusor underactivity; outcome; sacral neuromodulation; underactive bladder